Optimization Using Solvent-Free Microwave Hydro-diffusion Gravity Extraction of Onion Oil from Allium cepa by Response Surface Methodology - Yeni Variyana; Mahfud Mahfud (IPTEK The Journal for Technology and Science, 2019)
Extraction from Allium cepa using solvent-free microwave extraction (SFME) without solvent was chosen as a method in the extraction process. The method is combined with microwave hydro-diffusion gravity (MHG) technique. In this paper, onion oil was extracted from Allium cepa using solvent-free microwave hydro-diffusion gravity extraction which is as an alternative technique to produce onion oil and it has several advantages in terms of product quality and high yield. The highest yield was obtained from this research at 100 g, 450 W and 15 min is 2.5875%. Furthermore, response surface methodology (RSM) was designed to evaluate the effects of mass of raw material (g), microwave power (W) and extraction time (min) for optimization of experimental data. Response surface methodology gave the optimum condition at 99.738 g, 465.067 W, and 17.817 min is 2.677%. The error rates between the experimental and predicted model which are less than 5% indicate that values obtained in optimal conditions correspond to theoretical values and it can be used as a reference for optimizing